TROPICAL PALMS AND FACTORS INFLUENCING THEIR DISTRIBUTIONS AND DIVERSITY, WITH A FOCUS ON Pinanga DIVERSITY IN SOUTHEAST ASIA - Abdullah, Mohamad Farid; Md Jaafar, Salwana; Ahmad, Norhayati; Sukri, Rahayu Sukmaria (SEAMEO BIOTROP, 2024)
ARTICLE HIGLIGHTS- The palm genus Pinanga is the most diverse in Southeast Asia. - Limited ecological studies on Pinanga show the influence of environmental factors.- High Pinanga endemism in Borneo requires conservation action.ABSTRACTPalms represent some of the keystone species in tropical forests, providing numerous ecosystem services. They are widely studied by botanists because of their iconic and majestic appearance, although ecological studies of palm abundance, distributions, and diversity have only recently begun to gain attention. The abundance and diversity of palms at different spatial scales can be influenced by various factors, such as climate, soil properties, hydrology, topography and forest structure; understanding these influences is essential for conservation. This review details four abiotic factors (climate, soil chemistry, hydrology and topography) and one biotic factor (forest structure) affecting palm distribution and diversity. The genus Pinanga, one of the most diverse genera of palms, is discussed in terms of its distribution and diversity in Southeast Asia. Ecological studies on Pinanga diversity in the region are examined, revealing the influence of micro- and macro-scale variation in environmental factors, such as litter depth and thickness, canopy openness and crown cover, elevation, slope, aspect, light intensity, humidity and air temperature. The existing knowledge gaps on Pinanga ecology in Southeast Asia are discussed, and the need for more studies on population structures, functional traits and determinants of Pinanga diversity and distributions within different lowland forest types in the region are highlighted. The high endemism shown by Pinanga necessitates a more comprehensive ecological understanding of this genus to better inform its conservation and protection.